SENSATION SEEKING AND STRESS COPING STRATEGIES OF PARTICIPANTS IN MILITARY MISSIONS IN AFGHANISTAN AND ANTARCTIC EXPEDITIONS - Tatiana Iancheva; Galina Domuschieva - Rogleva; Milena Kuleva (Scientific Publishing House. NSA Press, 2018)
The activities performed by people who go on military missions or on Antarctic expeditions to Livingston Island often arise various questions and interpretations. On the one hand, they suppose a tendency toward risky acts; on the other hand, they require discipline and balance in one's behavior. The aim of our study was to examine the peculiarities of the need of security and the need of sensation seeking as basic personal variables of participants in military missions in Afghanistan and Bulgarian Antarctic expeditions and to examine their relation to the coping strategies applied. The research was done among 141 individuals (107 participants in Bulgarian military contingent which took part in an international NATO mission in Afghanistan in 2017 and 34 participants in two Bulgarian Antarctic expedition on Livingston Island in 2014/2015 and 2016/2017. All the individuals researched were divided into groups according to their age, gender and rank. We used: 1) Need of security assessment test (A. Velichkov, M. Radoslavova, S. Vassileva, V. Todorov, 1998). 2) Coping Orientations to Problems Experienced Scale - COPE - 1 (Carver, et al, 1989), adapt-ed for Bulgarian conditions (M. Georgiev et al, 2003) and 3) Research methods of psychic instability and sensation seeking, adapted by A. Velichkov and M. Radoslavova (2005). It is based on M. Zucker-man's methods (1979, 1994). The researched participants in military missions and the explorers from Antarctic expeditions showed significant differences along the indexes between the two groups. The participants in military mission have lower values along all scales of the need of sensation seeking in comparison with the established norms for the Bulgarian sample and higher values of the need of security. The results of the participants in the Antarctic expeditions are particularly interesting. Regardless of their pronounced inclination to adventurous experiences and risky behavior, to hasty and impulsive actions, when subjected to tension, uncertainty and stress they revert to cognitive engaged coping strategies, which suppose active coping, planning, mobilization and a sense of control over the situation. The established regularities are a valuable reference point both for the selection of the participants in military missions and expeditions and for the insurance of their safety.